2022
DOI: 10.3390/jcm11185354
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Glioblastoma: State-of-the-Art and Future Trends

Abstract: Glioblastoma (GBM) is a highly aggressive disease and is associated with poor prognosis despite treatment advances in recent years. Surgical resection of tumor remains the main therapeutic option when approaching these patients, especially when combined with adjuvant radiochemotherapy. In the present study, we conducted a comprehensive literature review on the state-of-the-art and future trends of the surgical treatment of GBM, emphasizing topics that have been the object of recent study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 171 publications
(252 reference statements)
0
4
0
Order By: Relevance
“…Several studies, including ours, have highlighted the fact that the average preoperative tumor volume is not a predictive factor of mortality; it correlates with age, symptoms, or the methylation status of the MGMT promoter [ 16 , 20 , 21 ]. Instead, the residual volume and, implicitly, the incomplete resection represent a risk factor for mortality, respectively determining a low survival [ 16 , 22 ]. Our research identified the presence of postoperative tumor volume as a risk factor for mortality (HR = 1.024), a result similar to the study conducted by Bette S et al (HR = 1.036) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, including ours, have highlighted the fact that the average preoperative tumor volume is not a predictive factor of mortality; it correlates with age, symptoms, or the methylation status of the MGMT promoter [ 16 , 20 , 21 ]. Instead, the residual volume and, implicitly, the incomplete resection represent a risk factor for mortality, respectively determining a low survival [ 16 , 22 ]. Our research identified the presence of postoperative tumor volume as a risk factor for mortality (HR = 1.024), a result similar to the study conducted by Bette S et al (HR = 1.036) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the surgical approach technique must involve new techniques such as fluorescent guidance, brain mapping techniques, intraoperative radiotherapy, optical coherence tomography, etc. [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations seeing the best outcomes suggest gross total resection with aggressive margin control of low-grade diffuse gliomas with wild-type IDH, with only subtotal resection for diffuse gliomas with mutated IDH[ 17 ]. In anaplastic gliomas, wild-type IDH tumors are conservatively treated with enhancing tissue resection, while those with mutant IDH can either be treated by total gross resection if they do not possess a 1p/19q codeletion or a subtotal resection if a 1p/19q codeletion exists in a functional area[ 17 , 18 , 19 ].…”
Section: Operative Treatmentmentioning
confidence: 99%
“…This RT and TMZ pharmacotherapy regimen was proposed by Stupp et al in 2005-the so-called Stupp protocol-when findings from a randomized controlled trial revealed that RT plus TMZ significantly improve the overall survival (OS) and progression-free survival (PFS) of newly diagnosed GBM patients compared to RT alone (14.6 vs. 12.1 months OS; 53.9% vs. 36.4% PFS at 6 months) (Stupp et al, 2005). GBM surgical resection is often challenging since the boundaries of the tumor are not easily distinguishable from the surrounding brain tissue, ultimately leading to tumor relapse due to the invasive potential of residual tumor cells (Sales et al, 2022). Apart from the SOC, four drugs and two medical devices are currently approved by the Food and Drug Administration (FDA) for the treatment of GBM (Figure 3): lomustine (1976), intravenous carmustine (1977), wafer implants of carmustine (Gliadel;1996: recurrent GBM;2003: newly diagnosed GBM), bevacizumab (2009, intratumoral thermotherapeutic iron oxide NPs (NanoTherm; 2010: recurrent GBM), and tumor treating fields (TTFs; Optune; 2011: recurrent GBM; 2015: newly diagnosed GBM) (de L azaro & Mooney, 2021).…”
Section: Gbm Treatment Options-standard Of Care (Soc) Limitations And...mentioning
confidence: 99%